Professor I. G. Freyman - the outstanding Soviet radio technician - V. G. Carpov (Известия высших учебных заведений России: Радиоэлектроника)
Article is prepared for printing L. I. Zolotinkina, is printed with some reductions concerning generally of the mathematical calculations confirming theoretical results of scientific researches I. G. Freymana. Reflection still of very important direction of works of I. G. Freyman connected with use of electrovacuum devices. In a number of its articles for the first time in domestic technical literature questions of terminology and determination of the main sizes characterizing operation of "hollow devices" were considered, methods of an assessment of quality of electron tubes are theoretically proved and offered. More than 60 publications and books are included into the list of scientific works of professor Freyman, practically all of them were the first scientific works in a number of the new scientific directions created as a result of development of radio engineering, considering the first publication - article A. S. Popova (1895).